1997
DOI: 10.1023/a:1018499015091
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The analysis of 19 populations of the grasshopper Eyprepocnemis plorans, collected along four rivers belonging to the Segura basin (Mundo, Benamor, Taibilla and Segura itself), has shown that the presence of B chromosomes ends abruptly in each river, coinciding with the existence of a narrow pass in which this grasshopper cannot live because of the absence of the appropriate habitats. The existence of a broad inland region lacking grasshoppers with B chromosomes suggests that B chromosomes arose after the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 4 publications
3
9
0
Order By: Relevance
“…This suggests higher isolation (i.e. lower gene flow) between the +B and -B populations and is consistent with the possibility that B chromosomes are absent in these latter populations because B chromosomes have not yet arrived to them [5].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This suggests higher isolation (i.e. lower gene flow) between the +B and -B populations and is consistent with the possibility that B chromosomes are absent in these latter populations because B chromosomes have not yet arrived to them [5].…”
Section: Discussionsupporting
confidence: 81%
“…plorans lives in moist habitats near river courses and coastal areas throughout the circum-Mediterranean region, also reaching the Caucasus and the Arabian Peninsula [3]. B chromosomes have been found in almost all natural populations of this subspecies so far analyzed from Spain, Morocco, Italy, Greece, Turkey, Armenia, and Dagestan [4], the only B-lacking region being located at the headwaters of the Segura River basin in Spain [5]. A recent study has suggested that B chromosomes in E. plorans plorans are rather young [6].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a same type of B in populations from Spain, Morocco, Tunisia and Sicilia suggests a recent invasion into these areas25. The high success of these B chromosomes, which are present in almost all populations hitherto analyzed, except those in the headwaters area of the Segura River basin in Spain26, has arisen from the transmission advantage (drive) they show during female meiosis27. This drive is suppressed by the A chromosomes2829 as a consequence of the arms race between A and B chromosomes predicted by the near-neutral model of B chromosome evolution30.…”
mentioning
confidence: 91%
“…In the Iberian Peninsula, B-lacking populations have only been found in the headwaters of several rivers belonging to the Segura river basin, including the Segura River itself and several of its tributaries (e.g. Mundo, Benamor and Taibilla) [ 14 ]. Since in each of these rivers the border between B presence and absence coincided with the existence of a geographical barrier, e.g.…”
Section: Introductionmentioning
confidence: 99%